Analisis Investasi Penyediaan Air Baku Untuk Pdam Tirta Dharma Duri (Intake Air Baku Sungai Rokan) - Syahrir, Alam; Siswanto, Siswanto; Komara, Rian Tri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
PDAM Tirta Dharma Duri is the only service provider of clean water Bengkalis thorn branch with sub-district service area Saber And District of Uptown. The PDAM Tirta Dharma spinesreceive water supply from PT Chevron Pacific Indonesia, with a small amount of clean water crisis that resulted in the service area. Responding to these conditions Bengkalis Governmentis determined to increase the supply of raw water to PDAM Tirta Dharma Thorns by building intake Sekapas River as one of the new raw water supply alternatives so that the water crisis that occurred can be overcome. This study examines the feasibility of the project Development of new raw water supply for PDAM Tirta Dharma Duris with intake Sekapas River. Investment feasibility indicator is the NPV (Net Present Value), BCR (Benefit Cost Ratio), IRR (Internal Rate of Return) and BEP (Break Even Point) as well as a sensitivity analysis. The cost of investment in this study uses data DED (Enginering Details desing) from the consultant planner RP. 203,254,685,215.00 with the results of the feasibility of aninvestment analyst for all parameters indicate the scope for further investment, due to the interest rate that is used by 13% showed the feasibility indicator, namely the value of apositive NPV, BCR values above 1 (one), the IRR is more of 13% (interest investment loans) and BEP less than 21 years.Keywords:Water supply, sensitivity analysis, NPV, BCR, IRR, BEP